In defense of minimally invasive spine surgery - John Entwistle; Girish K. Hiremath (Indian Journal of Neurosurgery)
Recently, minimally invasive techniques to address various lumbar spine pathologies have been developed. These techniques are associated with decreased approach-related morbidity, in addition to an accelerated postoperative recovery. In this article, we identify other factors, such as the maintenance of normal biomechanics, cost savings, as well as potentially the reduced need for reoperation that may be associated with the use of minimally invasive techniques, as compared with open surgical approaches.